2021
DOI: 10.1002/cmtd.202000056
|View full text |Cite
|
Sign up to set email alerts
|

The Guerbet Reaction Network – a Ball‐in‐a‐Maze‐Game or: Why Ru‐MACHO‐BH is Poor in Coupling two Ethanol to n‐Butanol

Abstract: The Guerbet reaction from two alcohols to a long-chain alcohol and water requires a redox catalyst and a strong base in homogeneous liquid systems. Especially, the reaction from ethanol to n-butanol is a challenging example of the reaction that suffers from low yields and selectivities in comparison with reactions of higher alcohols. The most important side reactions are the polymerization of acetaldehyde to C 6 + -components and the saponification of ethyl acetate under consumption of the base. This work purs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…For example, Beller and co‐workers have previously reported that 13 readily converts ethanol to ethyl acetate by acceptorless dehydrogenative coupling under mild reaction conditions [23a–b] . The conditions for such reactions are in open vessels to vent the hydrogen produced, i. e. analogous to Table 2, runs 13 and 15); under normal Guerbet conditions such catalysts are poor for ethanol‐ethanol homocoupling [23e] . We were intrigued as to whether these catalysts in the closed conditions for which we observe sec ‐butanol with tetradentate species would also produce this alcohol isomer.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Beller and co‐workers have previously reported that 13 readily converts ethanol to ethyl acetate by acceptorless dehydrogenative coupling under mild reaction conditions [23a–b] . The conditions for such reactions are in open vessels to vent the hydrogen produced, i. e. analogous to Table 2, runs 13 and 15); under normal Guerbet conditions such catalysts are poor for ethanol‐ethanol homocoupling [23e] . We were intrigued as to whether these catalysts in the closed conditions for which we observe sec ‐butanol with tetradentate species would also produce this alcohol isomer.…”
Section: Resultsmentioning
confidence: 99%
“…16 From a mechanistic viewpoint, Liauw explained why Ru-MACHO-BH performance is poor in stitching two ethanols to n-butanol. 17 For Ru-based catalysts, although Mazzoni reported the highest ethanol conversion, 16b the highest turnovers and TOF was demonstrated by Szymczak. 16c Guerbet reaction with 3dmetals is reported only with aromatic alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The reaction involves sequential two-fold dehydrogenation, aldol-condensation, and double hydrogenation. [1,2,[13][14][15][16][17] The primary product is 1-butanol, alongside hexanol, 2-ethylbutanol, octanol, 2-ethylhexanol, 3-ethoxybutanol, and traces of C 8 + aromatics. [1,2,16] Besides the use as solvent or building block for plasticizers, [18,19] also an application of the obtained mixture of C 4 + alcohols as a direct source for bio-based fuels with high octane numbers that can for example directly be used in diesel engines is discussed.…”
Section: Introductionmentioning
confidence: 99%